Raman spectroscopy and FTIR spectroscopy studies of Mn-doped CdSe QDs at different particles size - Hamizi, Nor Aliya; Johan, Mohd Rafie; Chowdhury, Zaira Zaman; Wahab, Yasmin Abdul; Al-Douri, Yarub; Saat, Asmalina Mohamed; Pivehzhani, Omid Akbarzadeh (Elsevier, 2019)
In this paper, we exclusively report on raman spectroscopy and fourier-transform infrared (FTIR) spectroscopy results and analysis of zinc blende manganese-doped cadmium selenide quantum dots (Mn-doped CdSe QDs) that synthesized using inverse Micelle technique with physical size ranging from 3 to 14 nm. Two significant peaks were observed correspond to the raman scattering by longitudinal optical (LO) of phonon and its first overtone (2LO) which located near ∼ 200 and 400 cm−1 under an exposure of 532 nm incident laser The role of oleic acid acid as a surfactant and capping agent shows in FTIR spectra.